Transcriptome analysis of bagging-treated red Chinese sand pear peels reveals light-responsive pathway functions in anthocyanin accumulation - Songling Bai (Nature Portfolio, 2017)
Abstract Bagging is an efficient method to improve fruit colour development. This work reported a transcriptome analysis using bagging-treated red Chinese sand pear peels. In total, 8,870 differentially expressed genes were further analysed by a weighted gene co-expression network analysis and early-, middle- and late light-responsive genes were identified. An annotation analysis revealed several pathways involved in the different responsive stages. The presence of LONG HYPOCOTLY 5, CRY-DASH and a CONSTANS-like transcription factors among the early light-responsive genes indicated the pivotal role of light, especially blue light, in the biological changes that occurred after bag removal. Other light-responsive transcription factors were also identified from the three light-responsive stages. In addition, the light-responsive pattern of anthocyanin biosynthetic genes differed among the biosynthetic steps. Although yeast-one hybrid assay showed that most of the structural genes were regulated by PpMYB10, their different temporal expressive pattern suggested that besides PpMYB10, other light-responsive transcriptional factors were also involved in the regulation of anthocyanin biosynthesis. In summary, our transcriptome analysis provides knowledge of the transcriptional regulatory network operating during light responses, which results in anthocyanin accumulation and other significant physiological changes in red Chinese sand pear peels after bag removal.